2018
DOI: 10.1080/08874417.2018.1432996
|View full text |Cite
|
Sign up to set email alerts
|

Information security policies’ compliance: a perspective for higher education institutions

Abstract: The aim of this investigation was to determine the reliability of normalizing rapid force (RF) production to peak force assessed during an isometric knee flexor assessment, and to present a novel method of classifying athletes' potential training needs within the 90À90 isometric hamstring assessment. Procedures: Twenty elite female soccer players (age: 20.7 § 4.7 years; height: 168.2 § 5.5 cm; body mass: 62.8 § 7.0 kg), with no recent (>6 months) history of hamstring strain injury, volunteered to participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…Multiple frameworks are available to assess human intentions towards information security policies, but none of the frameworks can be used as a standard behavioral process model. All the frameworks defined in the extant literature are either specific to a sector (for example, finance, higher education) [25,26] or specific to various theories [18,24,27]. None of the previous studies has made an effort to develop a consolidated information security behavior process which can exhibit the transformation process from noncompliance to compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple frameworks are available to assess human intentions towards information security policies, but none of the frameworks can be used as a standard behavioral process model. All the frameworks defined in the extant literature are either specific to a sector (for example, finance, higher education) [25,26] or specific to various theories [18,24,27]. None of the previous studies has made an effort to develop a consolidated information security behavior process which can exhibit the transformation process from noncompliance to compliance.…”
Section: Introductionmentioning
confidence: 99%
“…Digitizing the educational services makes the HEIs more targeted by cybersecurity attacks, like any other organization. However, HEIs lack the security awareness needed to handle these security issues ( Hina & Dominic, 2018 ). Therefore, they could use systems such as m-learning systems with security risks ( Badwelan, Drew & Bahaddad, 2016 ).…”
Section: Related Workmentioning
confidence: 99%
“…This could happen because there is neither standards nor guidelines to be applied or forced in HEIs. Moreover, most organizations do not monitor their users’ misbehavior ( Hina & Dominic, 2018 ). Since not all IT departments in higher education institutions/universities have the same experience and understanding of how important cybersecurity is, they do not treat it as a continuous process.…”
Section: Related Workmentioning
confidence: 99%
“…In the area of information security, personal responsibility is considered as the belief that an individual must take actions to achieve the goal of information security (LaRose et al, 2008). If individuals believe to a high extent that it is their responsibility to take control of security, this will increase the acceptable and proactive behaviors regarding information security (Anderson & Agarwal, 2010;D'Arcy & Greene, 2014;Workman et al 2008), while a lack of understanding of responsibility will result in noncompliance and breaches (Hina & Dominic, 2018). For example, Workman et al (2008) found that locus of control has a significant negative impact on subjective omissive behavior, indicating that individuals with a higher willingness to accept responsibility for information security will tend to practice information security measures.…”
Section: Hypotheses Developmentmentioning
confidence: 99%